Speech Acts in Peter Parker’s Utterances in The Amazing Spider-Man Movie and Its Relevance to English Curriculum: A Pragmatics Perspective - Fikri, Muhammad Husnul; Arafiq, Arafiq; Isnaini, Muh; Wilian, Sudirman (Journal of Authentic Research, 2025)
This study analyzes the speech acts in Peter Parker’s utterances in The Amazing Spider-Man (2012) movie and their relevance to the Indonesian Senior High School English Curriculum from a pragmatics perspective. Using Searle’s (1979) speech act theory, the research identifies four types of illocutionary acts, such assertives, directives, commissives, and expressives, while declaratives were absent. The qualitative analysis shows that assertives and directives are dominant, reflecting Peter’s dual identity as a teenager who informs and argues, and as Spider-Man who commands and requests in critical situations. The functions of these speech acts demonstrate how language is used to inform, request, commit, and express emotions based on context and intention. The findings also reveal that many utterances align with the curriculum’s communicative goals, particularly in expressing opinions, making requests, and showing feelings, suggesting that films can be authentic materials to enhance students’ pragmatic competence in English learning.